A new Late Cretaceous crocodyliform from the western margin of Gondwana (La Rioja Province, Argentina) - Fiorelli, Lucas Ernesto (2016)
The Cretaceous witnessed the greatest diversity of Gondwanan notosuchian crocodyliforms, which displayed high levels of diversity and a notable array of specialized forms that developed in different ecological niches. Among this diversity, the advanced notosuchians are a clade of mid body sized forms which displays a remarkable abundance but is restricted to two lithological units from the Late Cretaceous of South America, the Adamantina Formation in southestern Brazil and the Bajo de la Carpa Formation in Patagonia (Argentina). The only exceptions known so far were the Late Cretaceous Labidiosuchus from the Marilia Formation in Brazil and Yacarerani from the Cajones Formation in Bolivia. Herein we report a new Cretaceous crocodyliform, Llanosuchus tamaensis gen. nov. et sp. nov., found in the Los Llanos Formation (Campanian?) in northwestern Argentina (La Rioja Province). The small specimen includes well preserved fragments of the cranium and mandible with an estimated skull size of about 9 cm lengths. This crocodyliform shares several derived characters with Notosuchus terrestris from the Bajo de la Carpa Formation (Patagonia) and it was found in a weakly developed sandy paleosol profile formed in wet local conditions but in a region characterized by semi-arid climate and active eolian sedimentation. The presence of a new advanced notosuchian in the Cretaceous of western Gondwana, and its intermediate geographical region between the known South American species (Brazil, Argentina and Bolivia), has interesting implications, and adds another record of an advanced notosuchian in deposits with inferred warm climates and semi-arid paleoenvironments. Finally, Llanosuchus tamaensis supports a Late Cretaceous age for Los Llanos Formation with important geological implications for La Rioja Province.